Improving quality of life through sustainable energy and urban infrastructure in Africa - Shingirirai Savious Mutanga; Rainer Quitzow; Jan Christoph Steckel (Kiel Institute for the World Economy (IfW), 2018)
Focusing on critical aspects of infrastructure, such as energy, this paper argues that African countries, and African cities in particular, need infrastructure that advances both basic needs and industrialization, and avoids a lock-in of unsustainable, high-carbon technologies. G20 countries can promote and support quality of life in African countries by: (1) aligning and cementing the G20 Agenda for Africa with African initiatives, SDGs and the Paris Agreement, (2) mitigating economic risks of climate change through supporting low carbon development pathways in Africa, (3) creating and enabling a level playing field for low carbon technologies, which includes integrated strategies for derisking renewable energy investments, and (4) supporting smart and sustainable urban planning.
Keywords: Q01; Q54; H23; R11; 330; sustainable development; climate policy; Africa